SYSTEMIC INFLAMMATORY PROFILE IN PATIENTS WITH CHRONIC OBSTRUCTIVE PULMONARY DISEASE - Debreshlioska, Angjela; Angelovska, Irina; Pejkovska, Sava; Kirijas, Meri; Petlichovski, Aleksandar (Journal of Morphological Sciences, 2024)
Chronic obstructive pulmonary disease (COPD) is heterogeneous condition with various phenotypes that have their own pathogenetic mechanisms and certain inflammatory mediators, as C-reactive protein, interleukins, circulating leukocytes. Uncovering the inflammatory profile may identify disease biomarkers. We aimed to compare the values ​​of systemic inflammatory parameters ​​in patients with different clinical phenotypes and determine their correlation with clinical parameters. In 30 COPD patients we analyzed demographic and clinical data, history of allergies, cigarette smoking and history of exacerbations.  We phenotyped them into non-exacerbator, exacerbator and COPD with asthma phenotype. COPD assessment test, modified dyspnea scale and the BODE (Body mass index, Obstruction, Dyspnea, Exercise capacity) index were calculated. Spirometry and lung X-ray were performed. Peripheral blood was taken for analysis of inflammatory parameters. There were 16 patients (53.33%) with phenotype of non-exacerbator, and 7 (23.33%) with exacerbator and COPD with asthma phenotype each. COPD assessment test had significantly lowest value in non-exacerbator and modified dyspnea scale significantly highest value in exacerbator phenotype. There were no mild grade patients in exacerbator, and no very severe grade in nonexacerbator phenotype. C-reactive protein  and interleukin 8 had significantly lowest value in non-exacerbator; leucocytes significantly highest value in exacerbator; eosinophyls and interleukin 4 significantly highest value in COPD with asthma phenotype. There was no significant difference among the three phenotypes in neutrophyls and interleukin 18. The three clinical phenotypes: non-exacerbator, exacerbator and COPD with asthma have their own specific clinical and inflammatory features that have clinical, prognostic and therapeutic implications. Keywords: COPD, inflammatory parameters, phenotypes.